2019
DOI: 10.1128/aac.01715-18
|View full text |Cite
|
Sign up to set email alerts
|

APX001 and Other Gwt1 Inhibitor Prodrugs Are Effective in Experimental Coccidioides immitis Pneumonia

Abstract: Coccidioidomycosis is a systemic fungal infection caused by the inhalation of the arthroconidia of either of two closely related dimorphic fungi, Coccidioides immitis and C. posadasii, that are endemic in the southwestern United States and other areas in the Western Hemisphere. Chronic cavitary pulmonary infections and extrapulmonary sites of infection are very difficult to treat and often require lifelong azole therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
(60 reference statements)
0
26
0
3
Order By: Relevance
“…Furthermore, when higher ABT concentrations were evaluated (up to 250 g/ml), no antifungal activity was observed (7). Concordant with the lack of in vitro activity, ABT treatment alone did not enhance survival time nor reduce tissue fungal burden compared with infected mice without treatment in several animal models, including IPA (7), cryptococcal meningitis (8), or Coccidioides immitis pneumo-nia (9). Therefore, the survival benefit seen in mice receiving fosmanogepixϩABT is solely due to the effect of MGX.…”
mentioning
confidence: 86%
“…Furthermore, when higher ABT concentrations were evaluated (up to 250 g/ml), no antifungal activity was observed (7). Concordant with the lack of in vitro activity, ABT treatment alone did not enhance survival time nor reduce tissue fungal burden compared with infected mice without treatment in several animal models, including IPA (7), cryptococcal meningitis (8), or Coccidioides immitis pneumo-nia (9). Therefore, the survival benefit seen in mice receiving fosmanogepixϩABT is solely due to the effect of MGX.…”
mentioning
confidence: 86%
“…It targets the fungal-specific enzyme Gwt1, responsible for an early step in glycosylphosphatidylinositol (GPI)-anchor biosynthesis (Figure 1) [38]. This agent has demonstrated potency against multiple yeasts, moulds, and endemic mycoses [39]. Low MICs have been reported for Candida spp.…”
Section: Fosmanogepix (Apx001)mentioning
confidence: 99%
“…Arthroconidia are the infectious propagules of Coccidioides. Infection of murine models through intranasal delivery is the preferred and widely used method to understand Coccidioides pathology (Campuzano et al, 2020;Castro-Lopez & Hung, 2017;Hayden et al, 2019;Mead, Roe, et al, 2020;Viriyakosol, Kapoor, et al, 2019). Susceptibility to Coccidioides varies among mouse strains, with studies having shown that C57BL/6 and BALB/c mice are highly susceptible and that DBA/2 mice are more resistant (Kirkland & Fierer, 1983).…”
Section: Intranasal Infection Of Murine Modelsmentioning
confidence: 99%